2015
DOI: 10.1039/c4ra15833d
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and biological evaluation of small molecule-based PET radioligands for the 5-hydroxytryptamine 7 receptor

Abstract: A new prospective approach for PET imaging of 5-HT7 by a small molecule ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…2) a literature search made us realize that an arylimidazole 5-HT 7 R ligand was recently described, although no SAR studies were reported 46 . The compound, 5-(4-([ 11 C]methoxyphenyl)-1-methyl-4-nitro-1 H -imidazole, 2a , has been developed as a PET radioligand.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2) a literature search made us realize that an arylimidazole 5-HT 7 R ligand was recently described, although no SAR studies were reported 46 . The compound, 5-(4-([ 11 C]methoxyphenyl)-1-methyl-4-nitro-1 H -imidazole, 2a , has been developed as a PET radioligand.…”
Section: Resultsmentioning
confidence: 99%
“…After acquiring highly encouraging initial results for compounds 1a and 1b ( K i 5-HT7 = 385 nM and 50 nM, respectively, selectivity over 5-HT 1A R > 11-fold, Fig. 2 ) a literature search made us realize that an arylimidazole 5-HT 7 R ligand was recently described, although no SAR studies were reported 46 . The compound, 5-(4-([ 11 C]methoxyphenyl)-1-methyl-4-nitro-1 H -imidazole, 2a , has been developed as a PET radioligand.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding affinity of receptor‐ligands was calculated in terms of glide XP score. Interaction with 5HT 1A and 5HT 7 was performed with homology modelling as mentioned in our previous work [27] . The best pose was selected on the basis of glide score (G‐score) and the interactions formed between the designed ligands and active site of PDB.…”
Section: Resultsmentioning
confidence: 99%
“…Another specific agonist of 5‐HT 7, [ 11 C]PM20, has been evaluated in small animals which showed promising results. Subsequently, a new biaryl derivative 5‐(4‐(methoxyphenyl)‐1‐methyl‐4‐nitro‐1H‐imidazole with substituted azoles is also studied as a 5‐HT 7 PET ligand (Di Pilato et al, 2014; Shimoda et al, 2013; Tiwari et al, 2015). Unfortunately, both ligands were unable to reach the ideal level as a 5‐HT 7 PET ligand.…”
Section: Introductionmentioning
confidence: 99%